Left-handed DNA for efficient highly multiplexed imaging at single-protein resolution - Eduard M. Unterauer; Eva-Maria Schentarra; Isabelle Pachmayr; Taisha Tashrin; Jisoo Kwon; Sebastian Strauss; Kristina Jevdokimenko; Rafal Kowalewski; Felipe Opazo; Eugenio F. Fornasiero; Luciano A. Masullo; Ralf Jungmann (Nature Communications, 2025)
Abstract Multiplexed super-resolution microscopy enables spatial proteomics at single-protein resolution, but current methods often depend on secondary labels, complicating implementation and limiting throughput. We introduce a streamlined approach that combines speed-optimized DNA-PAINT sequences with their mirror-image analogs (left-handed DNA), enabling rapid and efficient 12-plex imaging. Validated on synthetic and cellular benchmarks, our method maps dense neuronal interactomes in 3D with 15 nm spatial resolution across a 200 × 200 µm2 field of view.